Identification and characterization of genetically divergent members of the newly established family Mesoniviridae - Zirkel, Florian; Roth, Hanna; Kurth, Andreas; Drosten, Christian; Ziebuhr, John; Junglen, Sandra (Journal of virology, 2013)
The recently established family Mesoniviridae (order Nidovirales) contains a single species represented by two closely related viruses, Cavally virus (CavV) and Nam Dinh virus (NDiV), which were isolated from mosquitoes collected in Côte d'Ivoire and Vietnam, respectively. They represent the first nidoviruses to be discovered in insects. Here, we report the molecular characterization of four novel mesoniviruses, Hana virus, Méno virus, Nsé virus, and Moumo virus, all of which were identified in a geographical region in Côte d'Ivoire with high CavV prevalence. The viruses were found with prevalences between 0.5 and 2.8%, and genome sequence analyses and phylogenetic studies suggest that they represent at least three novel species. Electron microscopy revealed prominent club-shaped surface projections protruding from spherical, enveloped virions of about 120 nm. Northern blot data show that the four mesoniviruses analyzed in this study produce two major 3'-coterminal subgenomic mRNAs containing two types of 5' leader sequences resulting from the use of different pairs of leader and body transcription-regulating sequences that are conserved among mesoniviruses. Protein sequencing, mass spectroscopy, and Western blot data show that mesonivirus particles contain eight major structural protein species, including the putative nucleocapsid protein (25 kDa), differentially glycosylated forms of the putative membrane protein (20, 19, 18, and 17 kDa), and the putative spike (S) protein (77 kDa), which is proteolytically cleaved at a conserved site to produce S protein subunits of 23 and 57 kDa. The data provide fundamental new insight into common and distinguishing biological properties of members of this newly identified virus family.